1994
DOI: 10.1002/1098-108x(199409)16:2<147::aid-eat2260160206>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Binge eating disorder and the proposed DSM-IV criteria: Psychometric analysis of the questionnaire of eating and weight patterns

Abstract: Proposed binge eating disorder (BED) diagnostic criteria were investigated to provide necessary psychometric characteristics and explore their utility in assessment. One hundred four subjects (52 self‐referred bingers, 52 comparison subjects) completed an initial administration of the Questionnaire of Eating and Weight Patterns (QEWP). The results supported the ability of the two core BED criteria (i.e., episodic overeating, loss of control) to discriminate between clinical and nonclinical binge eaters. Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 9 publications
0
78
0
Order By: Relevance
“…QEWP-R-based BED diagnosis is moderately stable over a 3-week interval ( ϭ 0.58) (32), correlates moderately with BED diagnosis based on structured interview ( ϭ 0.57) (33), and differentiates high-vs. low-frequency binge eaters with adequate predictive efficiency (71% to 73%) (32).…”
Section: Methodsmentioning
confidence: 99%
“…QEWP-R-based BED diagnosis is moderately stable over a 3-week interval ( ϭ 0.58) (32), correlates moderately with BED diagnosis based on structured interview ( ϭ 0.57) (33), and differentiates high-vs. low-frequency binge eaters with adequate predictive efficiency (71% to 73%) (32).…”
Section: Methodsmentioning
confidence: 99%
“…They completed the Questionnaire on Eating and Weight Patterns-Revised (QEWP-R; see Nangle, Johnson, Carr-Nangle, & Engler, 1994;Spitzer et al, 1992Spitzer et al, , 1993, as well as a self-report measure developed for this study. The self-report assessed attitudes toward diet, weight, Fijian cultural traditions concerning appetite and food, and media exposure.…”
Section: Procedures and Assessmentsmentioning
confidence: 99%
“…In multisite field trials, the QEWP distinguished binge eaters, nonbinge eaters, and bulimics on both weight and eating variables, including BMI, weight history, age of onset of obesity, dieting, and weight cycling Spitzer et al, 1993). Psychometric analysis (Nangle, Johnson, Carr-Nangle, & Engler, 1994) indicated that the BED diagnosis test-retest reliability from the QEWP was similar to test-retest reliabilities reported for other psychiatric disorders when the Structured Clinical Interview for DSM III-R (SCID) and the Diagnostic Interview Schedule (DIS) (Williams et al, 1992) were administered. The BED diagnosis was also moderately stable over a 3-week interval (kappa ¼ 0.58) (Nangle et al, 1994).…”
Section: Weight-related Pathologymentioning
confidence: 54%